f:{-3,-2,-1,0,1,2}→N,f(x)=x+3
Răspunsuri la întrebare
Răspuns de
1
f(x)=-3 ⇒x+3=-3 ⇒x=-6 ∉N
f(x)=-2 x+3=-2 x=-5 ∉N
f(x)=-1 x+3=-1 x= -4 ∉N
f(x)=0 x+3=0 x=-3 ∉ N
f(x)=1 x+3=1 x=-2 ∉N
f(x)=2 x+3=2 x=-1 ∉N
deci x∈∅
f(x)=-2 x+3=-2 x=-5 ∉N
f(x)=-1 x+3=-1 x= -4 ∉N
f(x)=0 x+3=0 x=-3 ∉ N
f(x)=1 x+3=1 x=-2 ∉N
f(x)=2 x+3=2 x=-1 ∉N
deci x∈∅
xFrank:
f:A→Z,f(x)=2x-1,A={x|x€Z,-3
Alte întrebări interesante
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă